ГИПОТЕЗА ЭФФЕКТИВНОГО РЫНКА В РАЗВИВАЮЩИСЯ СТРАНАХ В УСЛОВИЯХ «УЗКОЙ ТОРГОВЛИ», НА ПРИМЕРЕ СТРАН ПРИБАЛТИЙСКОГО РЕГИОНА (Journal of Economic Research & Business Administration, 2015)
This paper investigates efficient market hypothesis in the context of three Baltic markets Latvia, Estonia, and Lithuania. Paper takes account factors such as thin trading, nonlinearity, which negatively impact for emerging markets to be efficient. Using methodology proposed by Antoniou et. Al. 1997 that tests EMH in emerging markets we test EMH controlling for nonlinearity and thin trading. We assert that all three markets are inefficient. Moreover, after correcting for thin trading markets become efficient. However, we are in opinion of that factor of institutional evolutionis also important to be considered in our further study.